Coproduto desidratado de mandioca na alimentação de leitões na fase inicial - Castro, Davi Elias de Sá e (2016)
The objective of this research was to evaluate the nutritional value of Cassava Dehydrated Coproduct (CDC) and its effects on performance and blood variables of piglets fed different levels of CDC. In the first experiment, the digestible e test was carried out and 30 hybrid pigs averaging 18 (0.673) kg of initial weight (IW) were individually housed in metabolic cages and distributed in a completely randomized experimental design, with five treatments, 6 replicates and one animal per experimental unit. A basal diet was formulated to meet the nutritional requirements of the category and different levels of CDM (6, 12, 18 and 24%) were used to replace the reference diet, making the treatments. In the second experiment 120 piglets (60 males and 60 females) with initial weight of 13.05 (1.59) kg and final average weight of 26.03 (3.46) kg were distributed in experimental design of randomized blocks, with five treatments, six replicates and four animals per experimental unit. The treatments consisted of five diets with increasing levels of inclusion (0, 3, 6, 9 and 12%) of CDC. The corn and soybean meal based feed was formulated to meet the requirements for pigs in the initial phase. Data were subjected to statistical analysis and to present significant differences, the averages were compared by Dunnet test at 10% significance level. The digestibility assay revealed values of digestible energy and metabolizable energy of 3022 and 2984 kcal kg-1, respectively, in the natural matter of CDC. There was no effect (P>0.10) of CDC inclusion levels on final weight and average daily gain, however there was effect (P<0.10) of CDC levels on daily feed intake and feed conversion. The use of the CDC can be an alternative of energy source to feed piglets in the initial phase, and the inclusion of 2.56% of coproduct promoted maximum feed intake